Pengaruh Media Sosial, Citra Merek, Dan Persepsi Harga Terhadap Keputusan Pembelian N’pure Cleanser Gel Probiotics Pada Tik Tok Shop (Studi Kasus Pada Konsumen N’pure Di Kota Malang) - Alfiana, Fitria Tahta; Asiyah, Siti; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study expects to decide the Impact of Social Media, Brand Image, and Price Perception on Purchase Decision of N'pure Chemical Gel Probiotics on Tiktok Shop (Contextual analysis on N'pure customers in Malang City). A quantitative approach is used in this research method. The population that was used consisted of N'pure consumers in Malang City, and the malkhotra method was used to obtain 75 respondents. An online questionnaire is used for data collection. Using the IBM SPSS Statistics 27 program, multiple linear regression analysis was used to analyze the data. The study found that price perception, brand image, and social media influence all have a positive and significant impact on purchase decisions. Brand Image has a positive and significant influence on purchase decisions, Price Perception has a positive and significant influence on purchase decisions, and Social Media has no significant influence on purchase decisions. Keywords: Social Media, Brand Image, and Price Perception, Purchase Decisions